Projets de developpement pastoral. Resume des exposes et discussions - International Livestock Centre for Africa (1980)
Examines basic constraints to pastoral development. Looks into project financing, design and implementation. Discusses manpower development and training procedures. Includes notes on monitoring concepts and ILCA's monitoring activities.